Respuesta :
Answer:
Multiply each equation by the coefficient of y in the other one.
Step-by-step explanation:
(1) 6x + 5y = 2
(2) 4x + 2y = 8
Multiply each equation by the coefficient of y in the other one.
Multiply (1) by 2 and (2) by 5.
(3) 12x + 10y = 4
(4) 20 x + 10y = 40 Subtract (3) from (2)
8x = 36 Solve for x
x = 9/2
Answer:
Subtract 5 times the first equation from 2 times the second equation
Step-by-step explanation:
2(6x + 5y = 2)
5(4x + 2y = 8)
12x + 10y = 4
20x + 10y = 40
Subtracting the second equation from first gives:
−8x = −36
x =
−36
−8
x =
9
2